2016
DOI: 10.1080/07448481.2016.1179197
|View full text |Cite
|
Sign up to set email alerts
|

Victimization and suicidality among female college students

Abstract: Victimization is a significant and independent predictor of suicidality among college women. Controlling for relevant psychological health-related variables, college women who reported any of the 3 types of victimization had more than 8 times the odds of suicidality compared with nonvictims.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 35 publications
1
19
1
1
Order By: Relevance
“…No entanto, pesquisa realizada com estudantes americanos em 17 faculdades observou maior índice de violência sexual e uso de drogas ilícitas, além disso, muitos que praticaram esse tipo de violência já haviam sido vítimas em algum período da vida (10) . A violência sexual associada à emocional e física foi verificada também em estudantes de seis universidades espanholas, observando ainda maiores chances de tentativas de suicídio (11) .…”
Section: Discussionunclassified
“…No entanto, pesquisa realizada com estudantes americanos em 17 faculdades observou maior índice de violência sexual e uso de drogas ilícitas, além disso, muitos que praticaram esse tipo de violência já haviam sido vítimas em algum período da vida (10) . A violência sexual associada à emocional e física foi verificada também em estudantes de seis universidades espanholas, observando ainda maiores chances de tentativas de suicídio (11) .…”
Section: Discussionunclassified
“…Among the general population in Europe rates of physical victimization are approximately 4.0% (del Frate & van Kesteren, 2004), while the National Crime Victimization Survey (NCVS) estimates rates of violent victimization in the last 6 months to be approximately 2% in the United States (Morgan & Kena, 2017). However, studies have found higher rates of physical victimization, ranging from 11.7% to 26.3% (Coker, Follingstad, Bush, & Fisher, 2016;Leone & Carroll, 2016), among college student populations. In recent years, research has consistently identified high rates of physical victimization among male and female college populations in Europe (Björklund et al, 2010;Sánchez et al, 2017;Sánchez et al, 2016), Asia (Gover, Park, Tomsich, & Jennings, 2011), South America (Straus & Ramirez, 2007), and the United States (Messman-Moore, Ward, & Brown, 2009;Saewyc et al, 2009).…”
Section: Physical and Sexual Victimization Among College Studentsmentioning
confidence: 98%
“…However, studies have found higher rates of physical victimization, ranging from 11.7% to 26.3% (Coker, Follingstad, Bush, & Fisher, 2016;Leone & Carroll, 2016), among college student populations. In recent years, research has consistently identified high rates of physical victimization among male and female college populations in Europe (Björklund et al, 2010;Sánchez et al, 2017;Sánchez et al, 2016), Asia (Gover, Park, Tomsich, & Jennings, 2011), South America (Straus & Ramirez, 2007), and the United States (Messman-Moore, Ward, & Brown, 2009;Saewyc et al, 2009). In a study conducted in Northern Europe (Björklund et al, 2010), 29.1% of college students reported having ever experienced serious violence.…”
Section: Physical and Sexual Victimization Among College Studentsmentioning
confidence: 98%
See 1 more Smart Citation
“…This effect is attributed to the stigma of sexual violence and subsequent self-blame (Herman 1992;Jordan et al 2014;Resick 1993). Research has examined sexual violence among college students, along with the psychiatric implications, ranging from depression to dietary disorders (Brewer et al 2018;Carey et al 2018;Chang et al 2015;Kelley and Gidycz 2019;Leone and Carroll 2016;Stephens and Wilke 2016). In the past decade, universities have experienced increased sexual violence reporting rates and Title IX complaints, potentially due to the Obama administration's more proactive stance on Title IX enforcement (Musu-Gillette et al 2017;Wilson 2014).…”
Section: Introductionmentioning
confidence: 99%